KEEFEKTIFAN MEDIA SOFTWARE “TAGAINI JISHO” PADA MATERI KANJI N4 UNTUK PEMBELAJARAN MANDIRI (Mahasiswa Tingkat II Pendidikan Bahasa Jepang FKIP UR Tahun 2015/2016) - Putri, Astia Nurindah Kencana; Widiati, Sri Wahyu; Isnaini, Zuli Laili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to determine the effectiveness and feedback of media software "Tagaini jisho" on Kanji N4 lesson for individual learning. The Matching Pre test-Post test Control Group Design from quasi experiment used with restrictions of 20 people matching based on ownership of the laptop. Data collection techniques consist of tests (pre test-post test), assessment tests, questionnaires scale chart and interviews. Pre-test was used to test the homogeneity of the classes that have been matched. Post test is used to determine the significance after treatment.Based on statistical data processing SPSS, with two-tailed test, significance value was 0.576 greater than 0.05 (0.576> 0.05), Ha is rejected and Ho accepted. Media software Tagaini jisho is not effective on kanji N4 lesson for individual learning students level II of Japanese Language Education FKIP University of Riau. Based on data from questionnaires and interviews, student’s motivation in learning kanji are not so high, while student’s interest are high. Based on questionnaire data, media software Tagaini jisho can help in studying the kanji while based on interview data is impractical in learning kanji.Keywords: Effectiveness, media software, kanji, individual learning